Star Wars rebels : Ezra's gamble - Windham, Ryder (Disney/Lucasfilm Press, 2014)
"Fourteen year old Ezra lives alone on the outer rim planet of Lothal. He fends for himself by picking up odd jobs and hustling the unsuspecting Stormtrooper. Arena Day arrives--an underground tournament where mighty beasts battle to the finish and all the swindlers, gamblers, and no-gooders come from all corners of the planet to make a profit--Ezra is whisked into an unlikely partnership with the fearsome bounty hunter Bossk and enmeshed in a high-stakes chase against an endless fleet of troopers. Ezra isn't willing to trust anyone, but he soon learns that surviving doesn't always mean just fending for himself"--Back cover.